How (not) to think about theory-change in epidemiology. - Tulodziecki, Dana (Synthese)
My purpose in this paper is to show how a re-examination of Snow's famous South London water study (1853–1854), widely taken to have established that cholera is water-borne, highlights some problems with current, scientific realist accounts of theory-change. When examining scientific controversies, such accounts focus disproportionately on the 'winning' theories and their properties, or on those of the reasoning of the scientists who proposed them. I argue that this focus is misguided and leads us to neglect much of what is epistemically valuable in episodes of theory-change, thereby leading to inaccurate views about both the dynamics of theory-change and the notion of scientific progress that accompanies it. I end by sketching some implications for the philosophy of epidemiology.